Computational methods and classical-Marxian economics - Jonathan Cogliano; Roberto Veneziani; Naoki Yoshihara (Queen Mary University of London, School of Economics and Finance, 2020)
This article surveys computational approaches to classical-Marxian economics. These approaches include a range of techniques - such as numerical simulations, agent-based models, and Monte Carlo methods - and cover many areas within the classical-Marxian tradition. We focus on three major themes in classical-Marxian economics, namely price and value theory; inequality, exploitation, and classes; and technical change, profitability, growth and cycles. We show that computational methods are particularly well-suited to capture certain key elements of the vision of the classical-Marxian approach and can be fruitfully used to make significant progress in the study of classicalMarxian topics.
Keywords: C63; B51; B41; 330; Computational Methods; Agent-Based Models; Classical Economists; Marx